Variabilidade espacial de atributos que influenciam a produção de arroz vermelho irrigado no município de Apodi-RN - Nunes, Carlos Georg Fernandes (Universidade Federal Rural do Semi-Árido, 2008)
Rice crop area in Apodi River Valley, RN, Brazil, had a significant increase due to construction of Santa Cruz dam, which improved water availability downstream of the reservoir. Rice crop has been adversely affected by problems like disorganization of farmers, inefficient commercialization, product without added value, indiscriminate use of chemical inputs, loss of yield, decrease in plant vigor, and lower tillering. In this context, this work had as objectives to study causes of yield loss in irrigated red rice crop at Apodi River Valley; specifically, to study the effects of irrigation water used in that region and of soil salinity on red rice crop yield, besides to study spatial variability of physical and chemical soil characteristics of soil irrigated and cropped with red rice. The work was carried out in three small farms, where a georeferenced sampling grid was delimited with regular spacing, in which points were taken samples of soil and plants to determinate soil physical and chemical characteristics and, in two areas, yield components of red rice, allowing the use of geostatistics to study spatial variability. Rice yield and its components showed spatial dependence, which allowed the drawing of isovalue maps of the studied areas. Soil physical and chemical characteristics also showed spatial variability and correlated with rice yield components. The two studied areas showed different behavior in relation to spatial dependence and correlations. In the area of Francisco rice yield showed correlations mainly with distance to water inlet and with calcium to magnesium ratio, while in the area of Márcio the better correlation was with potassium
Spatial variability of soil attributes influencing irrigated red rice production in Apodi-RN, Brazil
Keywords: Oriza sativa L.; Soil salinity; Spatial variability; Geostatistics; Oriza sativa L.; Salinidade; Variabilidade espacial; Geoestatística; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM